2015
DOI: 10.1136/bmjopen-2015-008287
|View full text |Cite
|
Sign up to set email alerts
|

Is social deprivation an independent predictor of outcomes following cardiac surgery? An analysis of 240 221 patients from a national registry

Abstract: ObjectivesSocial deprivation impacts on healthcare outcomes but is not included in the majority of cardiac surgery risk prediction models. The objective was to investigate geographical variations in social deprivation of patients undergoing cardiac surgery and identify whether social deprivation is an independent predictor of outcomes.MethodsNational Adult Cardiac Surgery Audit data for coronary artery bypass graft (CABG), or valve surgery performed in England between April 2003 and March 2013, were analysed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 26 publications
4
27
0
Order By: Relevance
“…In Europe, data from the EUROASPIRE III survey of 13 935 patients showed older, female patients who did not have coronary artery bypass graft (CABG) surgery and those who smoked were less likely to attend . Consistent with the above findings regarding the centrality of financial/socioeconomic factors, numerous studies have also demonstrated social deprivation (eg, income, employment, and education) as a key factor associated with both low CR utilization and higher mortality …”
Section: Introductionmentioning
confidence: 75%
See 3 more Smart Citations
“…In Europe, data from the EUROASPIRE III survey of 13 935 patients showed older, female patients who did not have coronary artery bypass graft (CABG) surgery and those who smoked were less likely to attend . Consistent with the above findings regarding the centrality of financial/socioeconomic factors, numerous studies have also demonstrated social deprivation (eg, income, employment, and education) as a key factor associated with both low CR utilization and higher mortality …”
Section: Introductionmentioning
confidence: 75%
“…Variables were chosen for the multivariate analysis based on existing evidence indicating an association with initiation. [6][7][8][9][10][11][12] Independent variables were age, sex, ethnicity, marital status, IMD quintile, employment status, comorbidity count, prior cardiac event, diagnosis of diabetes mellitus, anxiety and depressive symptoms, risk factors, and referral indication. To take account of the nested nature of the data (ie, patients treated within CR centers), the Huber-White-sandwich estimator robust standard errors method was used.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…17 Using smoking as a surrogate for health behaviors in general, while overall epidemiological data are reassuring, there is a clear incongruity between the highest and lowest deprivation groups and this alone could cause differences in incidence and outcomes for HNC. 20,22,23 The aforementioned associations between socioeconomic status, surgical outcomes, risks factors for HNC, and previous work suggest that a relationship may indeed exist, 23,24 and in turn, there may be a notable health gradient outcome when applied to HNC also. 10 This can be significant, encompassing parameters such as Union Internationale Contre le Cancer (UICC) tumor stage, 19 length of hospital stay, 20 number of postoperative complications, 20,21 and overall survival (OS).…”
Section: Introductionmentioning
confidence: 91%